Suspending Dogma, Structuring Law: Legal Consciousness and the Niqāb Fatwa of Egyptian Scholar, Ali Gomaa - Jamjami, Lilik Abdul Malik; Cholila, Cholila (Indonesian Journal of Sharia and Socio-Legal Studies, 2026)
The responses of contemporary Muslim scholars (ʿulamāʾ), particularly in Egypt, to emerging social realities are frequently framed through the concept of fiqh al-wāqiʿ (Islamic jurisprudence of reality), yet the methodological framework underlying this concept remains underdeveloped. This ambiguity has led to a tendency to view Islamic legal reasoning primarily as a reactive response to external conditions rather than as a structured process of legal formation. Among contemporary scholars, Ali Gomaa presents a particularly significant case for examining how Islamic law is produced through interpretive practice. This study analyzes Gomaa’s Islamic legal reasoning on the niqāb (face veil) through a phenomenological lens to uncover the structure of legal consciousness underlying his fatwa. Using qualitative textual analysis, the study demonstrates that Gomaa’s rejection of the niqāb’s obligatory status is not merely a doctrinal conclusion but a methodological act grounded in the suspension of inherited dogmatic assumptions, a directed engagement with scriptural texts, and a reliance on lived communal practices as a horizon of legal meaning. His interpretive process mobilizes intentional structures of consciousness that mediate between textual evidence, juristic reasoning, and social experience. In doing so, Gomaa does not simply adapt the law to context but actively reconstructs legal meaning through a dynamic interaction between revelation and lived reality. This article argues that fiqh al-wāqiʿ, as reflected in Gomaa’s reasoning, should be understood as a socio-legal process of legal formation grounded in legal consciousness rather than merely as a descriptive framework for contextual legal adaptation. [Respons para ulama Muslim kontemporer, khususnya di Mesir, terhadap realitas sosial yang terus berkembang kerap dibingkai melalui konsep fiqh al-wāqiʿ (fikih realitas), namun struktur metodologis yang mendasari konsep tersebut masih belum berkembang. Ambiguitas ini telah mendorong kecenderungan untuk memandang penalaran hukum Islam terutama sebagai respons reaktif terhadap kondisi eksternal, alih-alih sebagai suatu proses pembentukan hukum yang terstruktur. Di antara para sarjana kontemporer, Ali Gomaa merupakan kasus yang sangat signifikan untuk mengkaji bagaimana hukum Islam diproduksi melalui praktik interpretatif. Studi ini menganalisis penalaran hukum Gomaa mengenai niqāb (cadar) melalui lensa fenomenologis guna mengungkap struktur kesadaran hukum yang mendasari fatwanya. Dengan menggunakan analisis tekstual kualitatif, penelitian ini menunjukkan bahwa penolakan Gomaa terhadap status wajib niqāb bukan semata-mata merupakan kesimpulan doktrinal, melainkan suatu tindakan metodologis yang berlandaskan pada penangguhan asumsi-asumsi dogmatis yang diwariskan, keterarahan intensional terhadap teks-teks keagamaan, serta penggunaan praktik hidup komunal sebagai horizon pembentukan makna hukum. Proses interpretatifnya menggerakkan struktur-struktur intensional kesadaran yang menengahi hubungan antara bukti tekstual, penalaran yurisprudensial, dan pengalaman sosial. Dengan demikian, Gomaa tidak sekadar menyesuaikan hukum dengan konteks, melainkan secara aktif merekonstruksi makna hukum melalui interaksi dinamis antara wahyu dan realitas hidup. Artikel ini berargumen bahwa fiqh al-wāqiʿ, sebagaimana tercermin dalam penalaran Gomaa, seharusnya dipahami sebagai suatu proses sosio-legal pembentukan hukum yang berakar pada kesadaran hukum, dan bukan semata-mata sebagai kerangka deskriptif bagi adaptasi hukum yang kontekstual.]